Pro-apoptotic effect of new quinolone 7- ethyl 9-ethyl-6-oxo-6, 9-dihydro[1, 2, 5]selenadiazolo [3, 4-h]quinoline-7-carboxylate on cervical cancer cell line HeLa alone/with UVA irradiation. (June 2016) - Jantová, Soňa; Mrvová, Nataša; Hudec, Roman; Sedlák, Ján; Pánik, Miroslav; Milata, Viktor
Abstract: 7- ethyl 9-ethyl-6-oxo-6, 9-dihydro[1, 2, 5]selenadiazolo [3, 4-h]quinoline-7-carboxylate (E2 h ) is a new synthetically prepared quinolone derivative, which in our primary study showed cytotoxic effects towards tumor cells. The aim of the present study was to examine the antiproliferative and apoptosis inducing activities of E2 h towards human cervical cancer cell line HeLa with/without the presence of UVA irradiation. Further, the molecular mechanism involved in E2 h -induced apoptosis in HeLa cells was investigated. Our results showed that both non-photoactivated and photoactivated E2 h caused morphological changes and inhibited the cell growth of HeLa cells in a time- and dose-dependent manner. Irradiation increased the sensitivity of HeLa cells to E2 h . Quinolone induced S and G2/M arrest and apoptosis in HeLa cells, as characterized by DNA fragmentation and flow cytometry. In addition, E2 h elevated the level of reactive oxygen species and activated caspases 3. In conclusions, E2 h alone/in combination with UVA irradiation induced apoptosis in HeLa cells through the ROS-mitochondrial/caspase 3-dependent pathway. Graphical abstract: Proposed model of molecular mechanism of selenadizoloquinolone-induced apoptotic death in HeLa cells Highlights: Selenadiazoloquinolone E2 h is a new potent photosensitizer. E2 h inhibited the growth of HeLa cells and induced S and G2/M arrest and apoptosis. UVA irradiation (dose 0.359 J cm − 2 ) increased derivative cytotoxicity. Changes in ROS level, mitochondrial potential and caspase 3 activity were found.